Adaptasi dan Validasi the Character Strength Inventory bagi Mahasiswa Indonesia - Wirda Hanim; Herdi Herdi (Universitas Pendidikan Ganesha, 2022)
No research specifically explores the dimensions of student character strength. The results of this study can be used as a pilot project to develop the dimensions of student character strength that can be used as a pilot project in education and guidance and counseling programs. This study aims to analyze the adaptation and validation of the character strength inventory for Indonesian students. This study uses the standard instrument adaptation and validation procedures from the International Commission Test (2016). This method was chosen because this study aims to adapt and test the psychometric properties of the CSI standard instrument for students as millennials in Indonesia. The sample of this study amounted to 741 students who were selected incidentally. Analyzing psychometric property data based on Item Response Theory includes item feasibility (item measure, item fit order, and instrument quality (unidimensionality, rating scale, item reliability, person reliability, and test reliability) using Rasch Model v. 3.73. The results show that SCI has good psychometric properties. Further studies are needed to examine the psychometric properties of SCI for high school students from various socio-demographic factors of participants.